RELATIONSHIP BETWEEN HUSBAND'S SUPPORT AND PREGNANT WOMEN'S COMPLIANCE IN CONSUMING BLOOD SUPPLEMENT TABLETS (Proceedings OPTIMAL, 2024)
Introduction: Lack of support from husband in remind his wife for always consume additional tablets blood can causes anemia in mothers pregnant. Condition This will result in complications Serious like birth premature, low birth weight low, or even maternal mortality. Research This aiming for know connection support husband with compliance Mother pregnant in consume additional tablets blood in Bragung Village Guluk-Guluk Subdistrict Sumenep Regency. Method: type study This is quantitative with approach cross sectional analytic. The population is all over Mother pregnant as many as 50 mothers pregnant. Technique of taking the sample with simple random sampling. Samples in study This a total of 33 mothers pregnant. Variable independent in research is support husband and dependent variable his is compliance Mother pregnant. Research instrument This use observation and questionnaire. Data processing with use editing, coding, scoring and tabulating. Statistical analysis of the test with chi square. Results: results study show part big husband give support for his wife a total of 23 respondents (69.7%), while for those who don't support a total of 7 respondents (30.3%) and some big Mother pregnant obedient in consume plus blood a total of 23 respondents (69.7%), while for those who don't obedient a total of 7 respondents (30.3%). The results of the study obtained p value = 0.024, ɑ = 0.05 means H1 accepted. Conclusion: There is connection support husband with compliance Mother pregnant in consume additional tablets blood. Suggestion: researcher furthermore can researchin gother variables that influence compliance Mother pregnant in consume additional tablets blood like factor Mother pregnant, support social, tablet factor added blood and factors culture.